Organización contable a la empresa comercial “El Torno” del Sr. José Camilo Abad Conde, del cantón Palanda, octubre-diciembre 2022. - Alberca Sarango, Mercy Rocío (2023)
The Curricular Integration project titled "Accounting Organization for the Commercial Company 'El Torno' owned by Mr. José Camilo Abad Conde, in Palanda Canton, October- December 2022, was conducted with the aim of providing a control tool for the resources available to the commercial company, thereby improving its effective development and performance. By implementing accounting practices in the commercial company 'El Torno', the set objectives have been achieved, which will help strengthen the financial management of the company and contribute to the growth and development of its commercial activities. The accounting process began with the development of a properly organized and coded chart of accounts, tailored to the company's needs, along with its corresponding account manual. This manual describes the concept and meaning of each account, the reasons for debit and credit transactions, and the balance of each account. These serve as support and guidance tools in the accounting process. Next, an initial inventory was prepared by conducting a physical verification of the assets owned by the company for its operation, as well as the obligations that initiate the accounting period. This led to the design of the initial financial position. Kardex cards and subsidiary accounts payable and receivable were then developed, recording detailed information obtained during the initial inventory, as well as the information provided by the owner regarding outstanding payments to suppliers and customers. Subsequently, based on the collected source documentation, daily journal entries were made for the transactions carried out during the study period. After preparing the general ledger, the accounts were summarized, and the trial balance was prepared. This information was further utilized to create a worksheet, which greatly assisted in the subsequent preparation of the financial statements with their corresponding explanatory notes. These financial statements provided a more accurate understanding of the economic and financial results for the accounting period. Implementing an accounting process is highly important for the commercial company 'El Torno' as it helps better organize and control its activities. Therefore, it is recommended that the owner of the company utilize this accounting system as a tool to stay informed about the current state of the company and facilitate decision-making for the development and utilization of its resources.